2014
DOI: 10.1073/pnas.1404402111
|View full text |Cite
|
Sign up to set email alerts
|

Rescuing US biomedical research from its systemic flaws

Abstract: The long-held but erroneous assumption of never-ending rapid growth in biomedical science has created an unsustainable hypercompetitive system that is discouraging even the most outstanding prospective students from entering our profession-and making it difficult for seasoned investigators to produce their best work. This is a recipe for long-term decline, and the problems cannot be solved with simplistic approaches. Instead, it is time to confront the dangers at hand and rethink some fundamental features of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
685
1
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 706 publications
(690 citation statements)
references
References 10 publications
3
685
1
1
Order By: Relevance
“…For institutions and individual researchers attempting to make long-term decisions, financial uncertainty makes planning very challenging. It is clear that simply putting more money into the system would provide only a temporary fix, not a long-term solution to the systemic problems with academic research ( Alberts et al , 2014; Martinson, 2007). …”
Section: Genesis Of the Future Of Research Symposiummentioning
confidence: 99%
See 1 more Smart Citation
“…For institutions and individual researchers attempting to make long-term decisions, financial uncertainty makes planning very challenging. It is clear that simply putting more money into the system would provide only a temporary fix, not a long-term solution to the systemic problems with academic research ( Alberts et al , 2014; Martinson, 2007). …”
Section: Genesis Of the Future Of Research Symposiummentioning
confidence: 99%
“…Hyper-competition can also discourage creative thinking and risk-taking, strong foundations of the scientific endeavor ( Alberts et al , 2014). Rather than grant applications for innovative, breakthrough science, we have observed that hyper-competition results in “safe” applications, driving incremental, slow improvements on existing knowledge.…”
Section: Genesis Of the Future Of Research Symposiummentioning
confidence: 99%
“…1 vaccination against some infections is a discussion point further in the paper The practical goal is the elimination of disease causes, rather than employing causes of health and prevention. Indicating a further distancing of research foci from health, it has been observed that B[o]vervaluing translational research is detracting from an equivalent appreciation of fundamental research of broad applicability, without obvious connections to medicine^ [6].…”
mentioning
confidence: 99%
“…Over the last three decades, and despite phenomenal advances in life sciences, plant science has failed to capture the imagination of this generation's (young) scientists. Whilst the number of PhD students enrolled in biomedical research doubled between 1982 and 2012, plant science PhD enrolments flat-lined (Alberts et al 2014;Jones 2014). This is at least in part due to the much-lamented stagnation in worldwide agricultural and plant science research funding (Butler 2008).…”
Section: How To Exploit the 'Omics Revolution' For Better Food Securitymentioning
confidence: 99%